2004
DOI: 10.1167/iovs.03-1304
|View full text |Cite
|
Sign up to set email alerts
|

Reading Acuity in Children: Evaluation and Reliability Using MNREAD Charts

Abstract: In children, MNREAD charts provide measurements of reading acuity as reliable as ETDRS chart measurements of distance acuity on a logMAR scale. They also provide highly reliable measurements of the maximum reading speed across all grades, independent of its noticeable increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
49
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 24 publications
13
49
3
2
Order By: Relevance
“…This differs from results by Virgili et al [31] who report a linear increase in CPS with grade level, which may be attributed to a difference in methods, charts used for testing and statistical analysis. The higher reading acuity score (larger size required) achieved by children under the age of 9 years suggests that even if time is not limited, children under the age of 9 years require a larger print size.…”
Section: Discussioncontrasting
confidence: 99%
“…This differs from results by Virgili et al [31] who report a linear increase in CPS with grade level, which may be attributed to a difference in methods, charts used for testing and statistical analysis. The higher reading acuity score (larger size required) achieved by children under the age of 9 years suggests that even if time is not limited, children under the age of 9 years require a larger print size.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, Subramanian and Pardhan 14 , established the repeatability of MNread acuity chart used similar criteria for subject recruitment (young university student aged 18 to 30 years) as in this study. High repeatability in maximum reading speed of Italian version of MNRead chart were found with the mean difference of ±0.077 wpm 15 , which were lower than Malay version (this study) and English version 14 Possible reason in the disparity of the outcome was younger participant than in this study since they used the children from Grade 3 to Grade 8 15 . Even though the UiTM-Muw reading chart showed a good repeatability, the reading rate was lower than MNRead acuity chart 14 .…”
Section: Reliability Of Repeatabilitycontrasting
confidence: 45%
“…In this study the ICC showed high reliability in the repeated measurements of the reading rate in the UiTM-Mrw reading chart as well as the UiTM-Muw reading chart i.e 0.85 and 0.81 respectively. Most of the testretest measurement in reading analyzed using the intraclass correlation coefficient to test the reliability of the repeated measurements 14,15,17 . The intra-class correlation coefficient was used to determine the consistency in the repeated measurements in reading performance evaluation 26 .…”
Section: Reliability Of Repeatabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] This test has also been used for age-specific reading performance in children in grades 3 through 8. 8 The MNREAD charts have not been used to study reading performance in individuals with albinism. Although this group has demonstrated variation in visual acuity, individuals do not have visual field defects or cognitive problems that might influence reading.…”
Section: Discussionmentioning
confidence: 99%